2002
DOI: 10.21273/hortsci.37.6.973
|View full text |Cite
|
Sign up to set email alerts
|

Maturation and Conversion of Somatic Embryos of Three Genetically Diverse Rose Cultivars

Abstract: Embryogenic callus cultures of three genetically diverse cultivars of rose (Rosa hybrida L.), the floribunda `Trumpeter', the multiflora `Dr. Huey', and the hybrid tea `Tineké', were used to study the effect of various carbohydrates and osmotically active compounds on somatic embryo maturation and conversion. Cotyledonary-stage embryos were produced by dispersing callus in liquid medium followed by filtration to isolate globular-stage embryos. Quantitative experiments were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…; Márquez-Martín et al 2011 ), and supplementing the medium with PEG or sugar alcohols, such as mannitol or sorbitol in rice ( Oryza sativa L.; Geng et al 2008 ). Myo-inositol, as an osmotic agent, has been less often used to improve SE quality, and only in rose ( Rosa hybrida L.; Castillón and Kamo 2002 ) and Norway spruce ( Picea abies (L.) H. Karst.…”
Section: Introductionmentioning
confidence: 99%
“…; Márquez-Martín et al 2011 ), and supplementing the medium with PEG or sugar alcohols, such as mannitol or sorbitol in rice ( Oryza sativa L.; Geng et al 2008 ). Myo-inositol, as an osmotic agent, has been less often used to improve SE quality, and only in rose ( Rosa hybrida L.; Castillón and Kamo 2002 ) and Norway spruce ( Picea abies (L.) H. Karst.…”
Section: Introductionmentioning
confidence: 99%
“…Almost all of the rose plants of cvs. Tineke, Mirabella, and Trumpeter regenerated from 2-year-old callus in a previous study (Castillon and Kamo 2002) produced phenotypically normal flowers, whereas many of the flowers of plants regenerated from 5-year-old callus of Classy and Kardinal in another study done simultaneously with this study (Fig. 1F) were phenotypically abnormal-the petals were malformed and the petals of cv.…”
Section: Conversion Of Embryosmentioning
confidence: 49%
“…The maximum conversion frequencies for Kardinal and Classy (58% and 28%, respectively) are among the highest reported for roses (see Introduction). Previously we reported a 13% conversion frequency for 2-year-old callus of Tineke (Castillon and Kamo 2002). The length of time the callus had been maintained in culture probably contributed to the decline in conversion frequency, as time in culture typically decreases regeneration rates and increases the phenotypic abnormalities of regenerated plants for most plant species.…”
Section: Conversion Of Embryosmentioning
confidence: 91%
“…Carbohydrates serve as energy and osmotic agents to support the growth of plant tissue (Lipavska and konradovah, 2004). Earlier findings in roses showed that sucrose is an important factor for somatic embryo maturation (Castillon et al, 2002;Kunitake et al, 1993). A number of studies have reported the enhancing effect of sucrose on somatic embryogenesis in several species (Korbes and Droste, 2005;Karami et al, 2006;Moon et al, 2013;Gholami et al, 2013).…”
Section: Resultsmentioning
confidence: 97%